2015
DOI: 10.1103/physrevb.92.184302
|View full text |Cite
|
Sign up to set email alerts
|

Carrier confinement and bond softening in photoexcited bismuth films

Abstract: Femtosecond pump-probe spectroscopy of bismuth thin films has revealed strong dependencies of reflectivity and phonon frequency on film thickness in the range of 25−40 nm. The reflectivity variations are ascribed to distinct electronic structures originating from strongly varying electronic temperatures and proximity of the film thickness to the optical penetration depth of visible light. The phonon frequency is redshifted by an amount that increases with decreasing film thickness under the same excitation flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…4. The parameters used for the extended two-temperature model agree well with previous results at moderate excitation density 10,23,24,28 . We found that the maximum lattice temperature T max is reached 15 ps after excitation, and 90% of the lattice temperature jump is complete within 5 ps.…”
Section: Modeling and Simulationssupporting
confidence: 82%
See 3 more Smart Citations
“…4. The parameters used for the extended two-temperature model agree well with previous results at moderate excitation density 10,23,24,28 . We found that the maximum lattice temperature T max is reached 15 ps after excitation, and 90% of the lattice temperature jump is complete within 5 ps.…”
Section: Modeling and Simulationssupporting
confidence: 82%
“…The parameters used in our model are summarized below. They agree roughly with the results of 28,31,32 15 W m -3 K -(1 27,28) Thermal Interface Conductivity C TI 1,950 W/cm 2 /K (23) Carrier Diffusion Constant D e 1,300 nm 2 /ps (31) Numerical solutions for the 20 nm and 275 nm films as a function of fluence for short and long timescales are shown below. Starting at 80 K, it takes 20 mJ/cm 2 for the 275 nm film to reach the melting point under this model, and over 50 mJ/cm 2 to reach the melting point plus the heat of fusion.…”
Section: Two-temperature Modelsupporting
confidence: 81%
See 2 more Smart Citations
“…Bismuth as a Peierls-Jones distorted semimetal [1] with its low equilibrium carrier density and its low effective masses is prone to carrier induced structural instabilities. One of them is the distinct displacive excitation of coherent A 1g optical phonons which has turned bismuth into one of the most studied materials by ultrafast timeresolved pump-probe techniques [2][3][4][5][6][7][8][9][10][11][12][13][14]. Upon photoexcitation the charge carrier density can be transiently increased by orders of magnitude thus drastically changing the potential energy surface of the atoms [9,10,15].…”
mentioning
confidence: 99%